Integrated Management of Seed Borne Pathogenic Fungi Of Brri 29 Rice Variety (Dhaka University Journal of Biological Sciences, 2022)
A pot experiment was conducted with the single and combined doses of fungicides, plant extracts and antagonist for the management of nine rice pathogens. A total of 13 treatments including controls with or without inocula of the pathogen were tested. Amongst all the treatments only T6 (Bavistin + Azadirachta indica + Trichoderma harzianum) showed highest percentage of seed germination and seedling vigor index of seeds inoculated with Alternaria alternata , Aspergillus flavus, Curvularia lunata and Pestalotiopsis guepinii. Next to T6, T10 (Bavistin + Tall + Azadirachta indica + Citrus medica) showed promising result against Drechslera oryzae, Fusarium moniliforme, Microdochium oryzae and Sarocladium oryzae. T3 treatment (Azadirachta indica) showed highest percentage of seed germination and seedling vigor index in case of seeds inoculated with Fusarium solani. Amongst all treatments the integrated use of Bavistin, A. indica and T. harzianum showed the better performance for growth reduction of test pathogens and increased germination of seeds.Dhaka Univ. J. Biol. Sci. 31(1): 159-168, 2022 (January)